Tradisi Riyadhah Pesantren - Khakim, Lukmanul (UIN Raden Mas Said Surakarta, 2020)
Pesantren is the oldest educational institution in Indonesia. Pesantren is a place for students to seek and deepen their knowledge of religion. Then in its development, each pesantren has its own characteristics or characteristics. In the pesantren tradition, students in the process of seeking knowledge have two dichotomies, namely with physical effort by studying seriously and by inner effort, namely by doing riyadhah or tirakat. The form of the riyadhah tradition between one pesantren and another also varies. In this paper, we will explore the riyadhah tradition that has developed and is still preserved in the Tegal Rejo Magelang Islamic Boarding School (API), the Darul Falah Jengkulo Kudus Islamic Boarding School and the Bustanu Usysyaqil Qur'an Tengaran Islamic Boarding School, Kab. Semarang which is in the form of fasting with various kinds of wazifa and its levels.